Factors Affecting Palm Farmers’ Decisions to Dispense Plantage-Product Zakat in Labuhanbatu Selatan Regency - Amalia Agustin Syn; Khalifah Muhammad Ali; Didin Hafidhuddin (Center of Strategic Studies (PUSKAS) BAZNAS, 2018)
Zakat is one of the five points in rukun Islam and consists of two types: zakat nafs (soul) and zakat maal (wealth). One of the many kinds of zakat maal is plantage-product zakat. Labuhanbatu Selatan Regency is an area that contains 160,785.04 hectares of palm plantation land as recorded in 2016. The area also produced 7,493,696.18 tons of Fresh Fruit Bunches (FFB) in the same year. The objective of this study is to identify the potential of plantage-product zakat (specifically palm plantage) and analyze the factors that affect farmers’ decision to dispense plantage-product zakat in Labuhanbatu Selatan Regency. Logistic regression analysis was the method of analysis used in this study. Based on data obtained from Dinas Perkebunan Provinsi Sumatera Utara 2016, the potential of plantage-product zakat in Labuhanbatu Selatan Regency reached 25.6 billion rupiahs in 2014; 21.6 billion rupiahs in 2015, and 370.4 billion rupiahs in 2016. The variables that significantly affected farmers’ decisions to dispense plantage-product zakat were comprehension of zakat, faith, rewards, Islamic study, and frequency of worship.